PENGARUH PENDIDIKAN KESEHATAN BERBASIS MEDIA AUDIOVISUAL TERHADAP CUCI TANGAN PAKAI SABUN (CTPS) PADA SISWA SEKOLAH DASAR SDN 040/IV KOTA JAMBI - Gilang egi kurniawan; Puspita Sari; Silvia Mawarti Perdana; M.Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of Clean and Healthy Living Behavior (PHBS) in schools, specifically the habit of Handwashing with Soap (CTPS), is still not optimal. At SDN 040/IV Jambi City, CTPS indicators were not met due to limited facilities and a lack of students' knowledge and attitudes. This low understanding increases the risk of infectious diseases such as diarrhea and ARI. Audiovisual-based health education was chosen for its effectiveness in combining sound and visual elements attractive to school-age children. This study aims to determine the effect of audiovisual-based health education on CTPS knowledge and attitudes among students at SDN 040/IV Jambi City.